An Analysis of Figurative Language in The Novel Let the Right One In - Noni Dwinka Lestari; Dhanu Ario Putra; Lina Tri Astuty Beru Sembiring (Literary Criticism, 2020)
This research discusses figurative language in the novel "Let The Right One In. This research has two objectives (1) To find out what kinds of figurative language are found in the novel "Let The Right One In". (2) To find out what kind of figurative language is more dominant. This study used the descriptive qualitative method This related to the description of the data in the form of a conversation and narrative. Analysis using domain analysis from Spreadly and theory from Keraf. The results of this study indicate that there are seven types of figurative language found, namely, simile, metaphor, personification, allegory, epithet, synecdoche, and eponym. Meanwhile, the dominant figurative language used in the novel "Let The Right One In" is the simile. Keyword: Semantics, Novel, Figurative language, Let The Right One In.